Analysis and NN-based control of doubly fed induction generator in wind power generation - Soares, Orlando (2012)
With the increasing size of wind power generation it is required to perform power system stability analysis that uses dynamic wind generator models. In this paper are presented all the wind power system components, including the turbine, the generator, the power electronic converter and controllers. The aim is to study the Doubly Fed Induction Generator (DFIG) operation and its connection to the power system, either during normal operation or during transient grid fault events. Two different control system design technologies are present, the first is performed by standard PI controllers and the second is based on artificial neural networks.